Formation of Blastocysts From Zona Pellucida–Free Oocytes: A Case Report on a Modified Technique in In Vitro Fertilization - Minh Tam Le; Trung Van Nguyen; Hong Nhan Thi Dang; Quoc Huy Vu Nguyen (Case Reports in Obstetrics and Gynecology)
Conclusions: By employing appropriate techniques for fertilization and embryo culture, ZFOs are capable of the development and production of good-quality blastocysts.